Derivation of new diagnostic reference levels for neuro-paediatric computed tomography examinations in Switzerland. (21st June 2018) - Wagner, Franca; Bize, Julie; Racine, Damien; Le Coultre, Régis; Verdun, Francis; Trueb, Philipp R; Treier, Reto
Abstract: Purpose. Definition of new national diagnostic reference levels (DRLs) for volume computed tomography dose index (CTDIvol ) and dose length product (DLP) for neuro-paediatric CT examinations depending on the medical indication. Methods . Paediatric cranial CT data sets acquired between January 2013 and December 2016 were retrospectively collected between July 2016 and March 2017 from eight of the largest university and cantonal hospitals that perform most of the neuro-paediatric CTs in Switzerland. A consensus review of CTDIvol and DLP was undertaken for three defined anatomical regions: brain, facial bone, and petrous bone, each with and without contrast medium application. All indications for cranial CT imaging in paediatrics were assigned to one of these three regions. Descriptive statistical analysis of the distribution of the median values for CTDIvol and DLP yielded values in the minimum, maximum, 25th percentile (1st quartile), median (2nd quartile), and 75th percentile (3rd quartile). New DRLs for neuro-paediatric CT examinations in Switzerland were based on the 75th percentiles of the distributions of the median values of all eight centres. Where appropriate, values were rounded such that the DRLs increase or at least remain constant as the age of the patient increases. Results. Our results revealed DRLs for CTDIvol and DLP up to 20% lower than the DRLs used so far in Switzerland and elsewhere in Europe. Conclusions. This study provides Swiss neuro-paediatric CT DRL values to establish optimum conditions for paediatric cranial CT examinations. Periodic national updates of DRLs, following international comparisons, are essential.